Evaluasi Point Reward Dalam Mendukung Strategi Bersaing PT Indosat, Tbk - , Siti Helwanisah; , Dr. Agus Setiawan, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Telecommunications is one of the most competitive industries in Indonesia. The increasing needs of faster and updated information among customers has leaded the rapid growth of National telecommunications industry. The Competition among mobile operators to obtain new customers (acquisition) as well as to retain existing customers (retention) is getting more attractive to be observed. Various efforts have been made by mobile operator in overcoming tight competition in order to maintain and increase the number of customers yet also to increase companyâs revenue. The main objective of this study was to determine and analyze the strengths, weaknesses, threats and opportunities of Business Unit Integrated Marketing PT Indosat Tbk in formulating competitive strategy. Data collection was carried out by using interview and questionnaire methods including brainstorming with couple of expertsâ people in the Business Unit. Initially, data collection acquired by using the Input Stage data in form of IFE, EFE and Matrix Competitive Profile while Matching stage using the IE Matrix and SWOT Matrix and Decision Stage by using QSPM. Based on researchâs findings, Business Unit of Marketing Strategic PT Indosat should utilize the intensive strategy through product development. The purpose of this product development strategy is to increase sales by improving existing products or develop new products with the orientation on customer satisfaction